Question: Substitution in Differential equation


I have to make following substitutions in a ODE:

alpha = x - 2

y(alpha) =  y(x) - 1


[Maple code starts]

The ode is 

ODE := diff(y(x), x) = (y(x)+1)/(x+2)-exp((y(x)+1)/(x+2));


I have used the following commands:

Rhsa := eval(rhs(ODE), {x = alpha-2, y(x) = y(alpha)-1});
lhsa:=subs({x = alpha, y(x) = y(alpha)}, lhs(ODE));


Sub_ODE:=lhsa = Rhsa;

[/Maple code]

Finaly I got the right ODE (as the ode is pretty simple and I have already done that anlaytically.)

The question is:


Is there a better way to do that substitution? 

Please Wait...